The Federal Reserve’s balance sheet and overnight interest rates: Empirical modeling of exit strategies - Marquez, Jaime; Morse, Ari; Schlusche, Bernd (Journal of Banking & Finance, 2013)
This paper provides a comprehensive study of the interplay between the Federal Reserve’s balance sheet and overnight interest rates. We model both the supply of and the demand for excess reserves. Treating outright securities holdings of the Federal Reserve as a policy tool, we estimate the effects of unconventional monetary policy on overnight funding rates. Further, we offer the first empirical assessment of the FOMC’s principles of the exit strategy. Assuming a path for removing monetary policy accommodation that is consistent with the FOMC’s exit principles, we project that the federal funds rate increases to 70 basis points by 2016, settling in a corridor bracketed by the discount rate and the interest rate on excess reserves, as excess reserves of depository institutions decline to near zero.